Simultaneous downregulation of miR-21 and upregulation of miR-7 has anti-tumor efficacy - Deepak Bhere (Nature Portfolio, 2020)
Abstract Dysregulation of miRNA expression has been implicated in cancer. Numerous strategies have been explored to modulate miR but sub-optimal delivery and inability to concurrently target multiple pathways involved in tumor progression have limited their efficacy. In this study, we explored the potential co-modulation of upregulated miR-21 and downregulated miR-7 to enhance therapeutic outcomes in heterogenic tumor types. We first engineered lentiviral (LV) and adeno-associated viral (AAV) vectors that preferentially express anti-sense miR against miR-21(miRzip-21) and show that modulating miR-21 via miRzip extensively targets tumor cell proliferation, migration and invasion in vitro in a broad spectrum of cancer types and has therapeutic efficacy in vivo. Next, we show a significantly increased expression of caspase-mediated apoptosis by simultaneously downregulating miR-21 and upregulating miR-7 in different tumor cells. In vivo co-treatment with AAV-miRzip-21 and AAV-miR-7 in mice bearing malignant brain tumors resulted in significantly decreased tumor burden with a corresponding increase in survival. To our knowledge, this is the first study that demonstrates the therapeutic efficacy of simultaneously upregulating miR-7 and downregulating miR-21 and establishes a roadmap towards clinical translation of modulating miRs for various cancer types.